Ethnomathematics-Based Math Quest (Mathematical Adventure Quest) to Enhance Critical Mathematical Thinking in Elementary Education - Salwa Sayidina Kansa; Dewi Tryanasari; Sri Lestari (LPPM STKIP Kusuma Negara, 2026)
Mathematical critical thinking skills are important skills that need to be developed in elementary school students. However, observations in grade V of SDN Jiwan 01 showed that students still had difficulties in analyzing contextual problems, determining solution strategies, and relating mathematical concepts to everyday life. This study aims to improve students' mathematical critical thinking skills through the application of ethnomathematics-based Math Quest (Mathematic Adventure Quest) media on the circumference of flat shapes. The study used a collaborative Classroom Action Research (CAR) method which was implemented in two cycles, including planning, implementation, observation, and reflection. The research subjects consisted of 26 grade V students of SDN Jiwan 01, Madiun Regency. Data collection techniques included observation, tests, and documentation. The results showed an increase in students' mathematical critical thinking skills after the application of ethnomathematics-based Math Quest media. The students' average score increased from 71.51 in the pre-cycle to 79.20 in cycle I and 86.89 in cycle II. The classical completion percentage also increased from 50% to 65.3% and 84.61%. Thus, the ethnomathematics-based Math Quest media effectively improves elementary school students' critical mathematical thinking skills.